Os sentidos de 'povo roraimense' em textos de parlamentares (1999 e 2005) - Leal, Maria do Socorro Pereira (2006)
This research has as its main issue the building process of the meanings of the expression povo roraimense in the state parliamentarians discourses when they refer to demarcation/homologation of the indigenous land Raposa Serra do Sol, in Roraima. The analysed cuttings are taken from Roraima Legislative Assembly sessions held, priorily, in 1999 (after the demarcation) and 2005 (after the homologation). This work is based in the Discourse Analysis theoretical pressupositions, as they are expounded in Michel Pêcheux s (France) and Eni Orlandi s (Brazil) works. In this perspective, the building process of the meanings is given by the linguistic-historical and ideological relation and, in the discourse, the images built are represented according to the subject position filled. The people involved in the indigenous land demarcation issue such as the politicians, their allies, their opponents, and the indians were studied in the way they were being denominated and determined in the roraimense political discourse. Two fields marked by a strong sense of opposition were delineated in terms of the indigenous land demarcation issue: demarcation in continuous area, negatively designated; demarcation in isolated areas, positively classified. Finally, the functioning of the expression povo roraimense was observed in relatio n to the ones involved in Raposa Serra do Sol land demarcation. Only the ones who propose and defend the land demarcation in isolated areas are defined as povo roraimense .